Conceptual Designs for Sustainable Aesthetics: creative chess sets where form follows meaning (Estudos em Design, 2021)
The paper presents conceptual designs that explore the notion of ‘sustainable aesthetics'. To encourage reflective practice through form and process, and guided by sustainable principles, a practice-based (thinking-and-doing) methodology was followed by Brazilian undergraduate design students. Beginning with a theoretical overview of the historical aesthetics of chess sets (premodern, modern and contemporary) the experimental findings show different approaches to thematic chess set designs that are guided by meaning-laden cultural considerations and developed using local, natural materials or reused (disposed) industrial materials. This is the first experiment of a project that represents a creative attempt to explore and develop an aesthetic for material culture through what we have termed a 'sustainable aesthetic function'. It demonstrates how objects with the same function can be expressed in very different ways whilst all adhering to the notion of "form follows meaning'.
Keywords: conceptual design; reflective practice; aesthetics; sustainability; form follows meaning